Preparation For Flight: The Physical Profile of Pre-Professional and Professional Circus Artists in the United States - Stephanie J Greenspan; Melanie I Stuckey (North American Sports Medicine Institute, 2024)
# Background Established norms for fitness and performance measures are lacking in circus arts. These would assist healthcare professionals and coaches to screen for readiness to participate in training or performance, determine post-injury return to performance, and develop targeted conditioning programs. # Purpose The purpose of this research was to establish norms for trunk and extremity physical exam and performance measures in circus artists by professional status, assigned sex at birth (ASAB), and age. # Study Design Descriptive laboratory study # Methods Circus artists (n=201; ages 13-69y; 172 females ASAB, 29 males ASAB) from 10 cities across the United States underwent a baseline physical examination including shoulder, hip and trunk measures of passive (PROM) and active (AROM) range of motion, measures of flexibility (shoulder and hip), strength (manual muscle tests, grip strength), cardiovascular fitness (3 minute-step test), balance (single limb and handstand), and performance, (pull-ups, and the closed kinetic chain upper extremity stability test \[CKCUEST\]). ANOVAs were used to determine between group differences by age and T-tests to discern differences by ASAB or professional status. # Results Differences existed by professional status for shoulder external rotation PROM, hip PROM, hip flexibility, shoulder and abdominal strength, and cardiovascular fitness. Sex differences were seen in active scapular upward rotation, hip and shoulder PROM and flexibility, hip and grip strength, and for functional performance measures (pull-ups, CKCUEST). Differences by age were limited to active scapular upward rotation, shoulder PROM, flexibility and strength, cardiovascular fitness, and balance. Overall, professionals outperformed pre-professionals for lower abdominal strength, pull-ups, handstand balance, cardiovascular fitness, hamstring, and straddle flexibility. Generally, males ASAB demonstrated greater shoulder flexibility and upper body functional strength while females ASAB had greater hip and lumbar flexibility and hip strength. No measures showed consistent declines with increasing age, though some showed differences between adolescents and adults. # Conclusion These normative values for physical characteristics and functional performance in pre-professional and professional circus artists may be used to guide screening for readiness to participate in advanced training or performance, return to performance after injury, and the development of targeted strength and conditioning programs. # Level of Evidence 3